2008
DOI: 10.1007/s11606-008-0620-2
|View full text |Cite
|
Sign up to set email alerts
|

Stop Orders to Reduce Inappropriate Urinary Catheterization in Hospitalized Patients: A Randomized Controlled Trial

Abstract: BACKGROUND: Hospitalized patients frequently have urinary catheters inserted for inappropriate reasons. This can lead to urinary tract infections and other complications.OBJECTIVE: To assess whether stop orders for indwelling urinary catheters reduces the duration of inappropriate urinary catheterization and the incidence of urinary tract infections. DESIGN:A randomized controlled trial was conducted in three tertiary-care hospitals in Ontario, Canada. Patients with indwelling urinary catheters were randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 22 publications
5
61
0
8
Order By: Relevance
“…1,5,6,8,15 Strategies to decrease the duration of catheterization have been recommended, such as reminding physicians to review whether a catheter is still appropriate and using automatic stop orders to facilitate the removal of catheters when the devices are no longer needed. 8,22 However, in 2 studies, 20,23 use of these approaches had no significant effect on the rate of UTIs. Using a before-and-after crossover design, Cornia et al 23 found that use of "computerbased order entry" did not significantly decrease the UTI rate.…”
Section: Characteristics Of the Patientsmentioning
confidence: 97%
“…1,5,6,8,15 Strategies to decrease the duration of catheterization have been recommended, such as reminding physicians to review whether a catheter is still appropriate and using automatic stop orders to facilitate the removal of catheters when the devices are no longer needed. 8,22 However, in 2 studies, 20,23 use of these approaches had no significant effect on the rate of UTIs. Using a before-and-after crossover design, Cornia et al 23 found that use of "computerbased order entry" did not significantly decrease the UTI rate.…”
Section: Characteristics Of the Patientsmentioning
confidence: 97%
“…However, similar to other studies [23,30], we found its use in the context of this study of limited value, as it failed to reflect important practice changes. Comparable intervention studies show similar results with respect to catheter use and CAUTI rate [6,11]; despite fewer catheter days [31] or reduced duration of inappropriate urinary catheterization [10], the CAUTI rate is not always reduced. This may be explained by how the CAUTI rate is calculated [3], i.e.…”
Section: Discussionmentioning
confidence: 87%
“…Diverse interventions that focus on limiting catheter use and on their prompt removal may significantly reduce CAUTIs [3, [9][10][11]. Education of nursing staff, electronic reminders aimed at reducing the duration of invasive devices [6,12], such as automatic stop orders [13], and the use of nurses specially trained to lead implementation projects (change champions) [12] have proved to be effective in changing practice and reducing CAUTIs [14].…”
Section: Introductionmentioning
confidence: 99%
“…A sensible solution therefore might bypass the physician altogether. For example, instituting automatic stop orders 7 and nursing advanced directives 8 to remove urinary catheters are 2 interventions that have previously been shown to be effective.…”
mentioning
confidence: 99%